Optional Management of Achalasia in 2021: Dilatation or Myotomy - Nabi, Zaheer; Ramchandani, Mohan; Reddy, D. Nageshwar (Journal of Digestive Endoscopy, 2021)
Achalasia cardia is a primary motility disorder of the esophagus, defined by lack of normal esophageal peristalsis along with inadequate relaxation of lower esophageal sphincter . The mainstay of management in achalasia includes pneumatic dilatation, Heller’s myotomy and peroral endoscopic myotomy (POEM). Pneumatic dilatation and Heller’s myotomy have gained maturity over several decades. The current best practice with regard to pneumatic dilatation is graded and on-demand dilatation in appropriately selected cases with type I and II achalasia. Laparoscopic Heller’s myotomy plus partial fundoplication is minimally invasive with reduced postoperative reflux and has virtually replaced open Heller’s myotomy with or without fundoplication. The subtyping of achalasia using high-resolution manometry bears prognostic significance and may help in choosing appropriate therapeutic modality in these patients. Since all the three modalities are effective for type I and II achalasia, the choice among these depends on the availability, expertise, and patient’s preferences. On the other hand, POEM is more effective than pneumatic dilatation and Heller’s myotomy and, therefore, preferred in type III achalasia. Although POEM is effective across the spectrum of esophageal motility disorders, the incidence of gastroesophageal reflux is high and needs to be considered while choosing among various options in these patients. In cases with failed POEM, redo POEM appears to be effective in alleviating symptoms.
Keywords: esophagus; achalasia; endoscopy; treatment; Heller’s myotomy; per-oral endoscopic myotomy